Rethinking “Anthropoholism as an Authentic Tool for Environmental Management” - Egbeji, Patrick Odu (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
The quest for the most feasible approach to environmental management has assumed priority today because of the many links established between the environment and sustainable development. This quest has taken the centre stage beyond parochial considerations and practices into a unique discipline of its own known as environmental ethics because of the excruciating consequences that environmental degradation is already posing the present generation with impending dangers for the future. It is along with this vision of a feasible environmental management approach that this paper critically examines the theory of “anthropoholism” which claims to bridge the gap between anthropocentricism and holistic environmental ethics. Using the critical and exploratory approaches, the work appraises the theory of “anthropholism” indicating that although it makes gleeful insights as to the indispensability of human beings in inaugurating a workable approach for environmental management and makes a place for different worldviews, it is too concise in its self-expression for a new theory, etymologically problematic and too simplistic in the application of concepts it drives from, downplays the self-regulating abilities of the ecosystem and exposes human species to danger within the larger context of the ecosystem. The work recommends that equilibrium ethics away from mere linguistic classification of approaches into anthropocentric and non-anthropocentric prototypes is the way forward for feasible environmental ethics.